Access to health data for scientific research. Remarks in the light of Article 40 DSA - Greser, Jarosław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The primary objective of the Digital Services Act is to enhance the transparency of the operations of VLOPs and VLOSEs. This is achieved by ensuring the possibility of effective control by public entities and by preventing negative phenomena covered by systemic risks through research by independent researchers. However, the data that VLOPs and VLOSEs collect as part of their services can also be used for research for public good. This is particularly relevant in the case of information on the health status of their users. This data can be important in the development of new health products and services and for the planning of public policies in this area. This article explores whether the access to data provided for in Article 40 of the Digital Services Act allows for research in health-related areas. The article is divided into four parts. The first part examines the concept of health data, and the second considers whether medical data falls within the purposes of allowing data sharing. The third part of the article analyses the conditions that limit the release of data for research purposes. The final part of the article contains conclusions andpoints out that the Digital Services Act allows health information to be made available for scientific research in this area, but that this is very limited by the conditions ntained in the act. However, the interpretation of these conditions can vary, and it largely determines how much and what data researchers can receive in practice. Consequently, the role of the Digital Services Coordinators is of great importance in shaping the practice of fulfilling data access requests.
Keywords: health data; open science; VLOP; VLOSE; Digital Service Act; access to data